Fabrication and assessment of performance of clay based ceramic membranes impregnated with CNTs in dye removal - Kareem H. Hamad; Heba Abdallah; Sohair T. Aly; R. Abobeah; Sh. K. Amin (Scientific Reports)
Abstract In this research, flat disk clay-based ceramic membranes were fabricated and optimized for use in the treatment of wastewater contaminated with dye. The properties of the fabricated membranes were assessed to optimize the fabrication conditions, namely, the firing temperature (1150 °C, 1200 °C, and 1250 °C), soaking time (30 min and 60 min) and zeolite percentage (0%, 10%, and 20%). On the other hand, the rejection of methylene blue dye (MB) and acid fuchsin dye (AF) was studied. The surface of the optimal membrane support was modified using functionalized COOH-carbon nanotubes to increase the dye removal percentage. The fabricated membranes were characterized using FTIR, XRD, and XRF. The optimum membrane support was fabricated at 1150 °C, after 30 min of soaking and with 0% zeolite. The most suitable membrane support was found to be AF, as its rejection percentages reached 42% and 95% without and after surface modification, respectively. The surface of the membrane was examined via SEM, which revealed normally distributed pores. The average pore size of the final membrane was found to be 0.076 micrometers using a mercury porosimeter; thus, the produced membranes can be used in ultrafiltration applications. Finally, the fouling properties showed that the total fouling reached 72.8%, of which only 2.1% was irreversible.